1999
DOI: 10.1016/s0014-5793(99)00704-8
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatitis B virus mutants: significance of molecular changes

Abstract: Human hepatitis B virus, the leading pathogen for hepatitis B, is a compact DNA virus with viral genes that largely overlap. An increasing number of mutations have emerged following human interventions such as vaccination and anti-viral therapy. While vaccine escape mutants are characterized by mutations on the antigenic hepatitis B surface antigen, those carrying mutations in other viral proteins are either resistant to anti-viral therapy or implicated in acute liver diseases. Molecular identification of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 76 publications
(94 reference statements)
0
35
0
2
Order By: Relevance
“…The real-time PCR assay was able to quantify HBV DNA even at low levels in subsequent follow-up samples and monitor the ef®cacy of antiviral treatment. Sensitive HBV DNA assays, such as the real-time PCR, allow also the detection of various HBV mutants that may remain undetectable using classical screening assays [Chen and Oon, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…The real-time PCR assay was able to quantify HBV DNA even at low levels in subsequent follow-up samples and monitor the ef®cacy of antiviral treatment. Sensitive HBV DNA assays, such as the real-time PCR, allow also the detection of various HBV mutants that may remain undetectable using classical screening assays [Chen and Oon, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence indicates that HBV can indirectly induce HCC by eliciting host immune responses against the infected hepatocytes [12,13]. Furthermore, several lines of evidence have demonstrated that naturally occurring mutants in the S region correlate with a more progressive form of liver disease [14,15]. In particular, antiviral drug therapies related to the C terminal truncated S proteins have been reported to potentially contribute to hepatocarcinogenesis through an increase in its transactivating capacity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These include noticeably HBV viral infections, which account for more than 80% of HCC cases in Asia (Chen and Oon, 1999;Wang et al, 2002). In the case of HBV infection, the risk of developing HCC for chronic HBV carriers is increased by a factor of 100 as compared with a non-infected individual (El-Serag et al, 2001).…”
Section: Introductionmentioning
confidence: 99%